Developing Sustainable High-Volume Fly Ash Concrete with Enhanced Self-Consolidating Capabilities - Yogie Risdianto (Yayasan Banu Haji Samsudin, 2025)
This study explores the potential of high-volume fly ash concrete (HVFAC) with enhanced self-consolidating capabilities as a sustainable alternative to traditional concrete. The primary issue addressed is the environmental impact of cement production, which contributes significantly to CO2 emissions. The study aims to optimize the use of fly ash in concrete mixtures to reduce CO2 emissions while maintaining concrete's strength, workability, and durability. A library research methodology was employed, analyzing existing literature on HVFAC, self-consolidating concrete, and sustainable concrete development. The research reveals that while high fly ash content can slightly reduce early-age strength, it enhances long-term durability and resistance to chemical attacks. The integration of superplasticizers is essential to improve self-consolidating properties, allowing the concrete to flow smoothly without mechanical compaction. Additionally, the study emphasizes the significant environmental benefits of HVFAC, including reduced CO2 emissions and resource conservation. However, challenges remain in optimizing the mix design and achieving a balance between fly ash content, strength, and workability. The research concludes that HVFAC has substantial potential for sustainable construction practices, provided that future research addresses the remaining challenges and refines mix designs for broader application.